Manual of basic techniques for a health laboratory - World Health Organization (Geneva : World Health Organization, 2003)
Manual intended for the use of laboratory personnel in developing countries. Cost, reliability and simplicity of the method, along with availability of resources for small laboratories, are considerations in the selection of techniques
Keywords: Laboratory Techniques and Procedures -- handbooks; Clinical Laboratory Techniques -- methods -- handbooks; Developing Countries -- handbooks